Dendritic Cell-Based Immunotherapy in Lung Cancer - Stevens, Dieter; Ingels, Joline; Van Lint, Sandra; Vandekerckhove, Bart; Vermaelen, Karim (Frontiers in Immunology, 2021)
Lung cancer remains the leading cause of cancer-related death worldwide. The advent of immune checkpoint inhibitors has led to a paradigm shift in the treatment of metastatic non-small cell and small cell lung cancer. However, despite prolonged overall survival, only a minority of the patients derive clinical benefit from these treatments suggesting that the full anti-tumoral potential of the immune system is not being harnessed yet. One way to overcome this problem is to combine immune checkpoint blockade with different strategies aimed at inducing or restoring cellular immunity in a tumor-specific, robust and durable way. Owing to their unique capacity to initiate and regulate T cell responses, dendritic cells have been extensively explored as tools for immunotherapy in many tumors, including lung cancer. In this review, we provide an update on the nearly twenty years of experience with dendritic cell-based immunotherapy in lung cancer. We summarize the main results from the early phase trials and give an overview of the future perspectives within this field.